DIGITIZATION OF VILNIUS UNIVERSITY LIBRARY COLLECTION GDL COURT BOOKS: FROM PRODUCTION OF IMAGES TO CREATION OF A RESEARCH TOOL - PROKOPČIK, MARIJA; TIMČENKO, TATJANA (Knygotyra, 2013)
The article deals with reasons for the choice of GDL Court Books collection preserved at Vilnius University Library (VUL) as digitization and research object. It presents VUL experience with digitization projects, need for creation of additional digitization projects values and services. The article aims to reveal specific features of database of digitized manuscripts as a result of and resource for scientific research. It analyses criteria for selection of this particular collection: importance for researchers in history, language and culture, outcomes of intensive use, means for improvement and (or) stabilisation of physical conditions of the collection, etc. Digitization activities and their development in VUL are based on idea, that digitization is not only production of imagages. Digitized documents should be supplied with metadata produced by collaborative efforts of researchers and librarians, that enable multiaspect access to information and data as well as possibility to use these enriched documents as a source for further investigation and research. Preparation of documents for digitization is an important though often undervalued stage of each digitization project. Implementation of simple procedures such as informed choise of equipment, microbiological prevention and dust cleaning could warrant preservation of documents and safety of staff. Conservation decisions are part of this preparatory stage as well. They often depend on attitudes towards documents authenticity preservation, however in any case on this stage it is possible to reveal important information about the history of digitized documents, even discover new documents and (or) their fragments. Due to specificity of Court Books’ contents and form, description of documents, contained in the Books are presented using Text Encoding Innitiative (TEI P5) Manuscript description schema that makes it possible to use originally spelled and structured personal names and place-names, to record interpersonal relations, links between persons and places, etc. Possibility to use already approved and functioning controlled tool – BAVIC thesaurus for creation and use of Court Books database could be helpfull in solving problems of personal and place names as well as chronology diversity, to avoid duplication of activities and to integrate new database into common Lithuanian infrastructure of digitized cultural heritage objects.